PENGEMBANGAN PERANGKAT PEMBELAJARAN DENGAN PENDEKATAN CTL PADA MATERI TEOREMA PYTHAGORAS DI KELAS VIII SEKOLAH MENENGAH PERTAMA - Muâti, Yafita Arfina; Mardiyana, Mardiyana; Sari Saputro, Dewi Retno (Journal of Mathematics and Mathematics Education, 2017)
Abstract: This study aimed to: (1) produce teaching and learning materials with CTL approach on Pythagorean theorem at VIII Grade of Junior High School that was valid, practical, and effective, (2) investigate the better achievement in mathematics, whether using teaching and learning materials of CTL approach than using conventional teaching and learning materials. This study was development research. The development model used in this research was a developmental  research by  Plomp that contained five phases, (1) preliminary investigation, (2) design, (3) realization/ construction, (4) test, evaluation, and revision, and (5) implementation.  Teaching and learning materials said have quality if fulfilled validity, practical, and effective criteria. Teaching and learning materials was categorized validity based on expert judgement. Taeching and Learning materials was categorized practical if based on theory, teaching and learning materials was able to use it without revision or little revision and had fulfilled criteria of a practical teaching and learning materials. Teaching and learning materials was categorized effective if it fulfilled the indicators for a effective learning, including students activity during studying, learning activities based on syntax, student response about the learning, and students learning result. The data in this research was collected using test, questionnaire, observation, documentation, and interview.  To investigate the better student achievement used t-test. The results of this study were as follows: teaching and learning materials of CTL approach that include lesson plans, worksheets, and test of learning outcome was said to be valid, practical, and effective. Besides  that, student achievement with teaching and learning materials of CTL approach was better than student achievement with teaching and learning materials of conventional approach.Keywords: Teaching and learning materials, CTL, Pythagorean theorem